﻿Phenytoin concentration in people with epilepsy: a comparative study in serum and saliva - Angel Alvarado; Gregoriana García; Alexis Morales; Gustavo Paredes; Miriam Mora; Ana María Muñoz; Ricardo Pariona; María R. Bendezú; Haydee Chávez; Jorge A. García; Doris Laos-Anchante; Berta Loja-Herrera; et al. (Pensoft Publishers, 2022)
In clinical practice, therapeutic drug monitoring (TDM) makes it possible to measure the concentration of drugs in serum or saliva, the purpose of which is to reduce adverse effects and optimize pharmacological therapy. The objective was to determine the concentrations of Phenytoin in saliva and serum of people with epilepsy. Cross-sectional, descriptive study with dynamic recruitment of 30 people with epilepsy (n = 30; 17 men, 56.7% and 13 women, 43.3%; mean age 33.9 ± 11.83 years). Serum and saliva samples were collected at trough levels from patients, who were under phenytoin treatment for at least three months. Drug levels were assessed by the Cloned Donor Enzyme Immunoassay method. Phenytoin levels were found in saliva between 0.01 to 3.56 mg/L and in serum between 0.09 to 36.60 mg/L. Pearson's analysis showed an association between the estimated serum and saliva phenytoin concentrations (R2 0.7026; 95% CI 0.685-0.921), with a significant statistical correlation (p < 0.05). The Bland-Altman test broke concordance, the difference between the two saliva/serum methods is within 95% confidence. It is concluded that there is an association and concordance between the concentrations of phenytoin in serum and saliva, therefore, this technique can be useful in the clinical monitoring of phenytoin.